Microstructure and tensile properties of ODS ferritic steels mechanically alloyed with Fe2Y. (December 2016) - Macías-Delgado, J.; Leguey, T.; de Castro, V.; Auger, M.A.; Monge, M.A.; Spätig, P.; Baluc, N.; Pareja, R.
Highlights: An ODS ferritic steel has been produced by mechanical alloying with Fe2 Y. Microstructure shows homogeneous precipitation of Y-Ti nano-oxides. Tensile properties from RT to 973 K are reported. Abstract: An oxide dispersion strengthened ODS ferritic steel has been produced by mechanical alloying of Fe–14Cr–2W–0.2Ti (wt.%) prealloyed powder with 0.55 (wt.%) Fe2 Y intermetallic particles and consolidated by hot isostatic pressing. The microstructure after thermal treatments confirms the homogeneous precipitation of Y-Ti oxides with nanometric sizes. Tensile properties as a function of the testing temperature from room temperature to 973 K have been measured and the results are discussed with respect to similar ODS ferritic steels fabricated by a powder metallurgy route using Y2 O3 powder.